Differential Analysis and Application Prospects of DNA Tumor Biomarkers in The Five Major Types of Tumors - Jiang, Yunzhen; Wang, Ruofan (Transactions on Materials, Biotechnology and Life Sciences, 2024)
With the increasing global burden of cancer, the study of tumor biomarkers (TMs) is of great significance as key tools for early diagnosis, disease monitoring, treatment efficacy evaluation, and prognosis judgment of cancer. This study focuses on the five major tumor types: lung cancer, colorectal cancer, liver cancer, female breast cancer, and gastric cancer. By screening and integrating relevant data on the clinVar website, this article classified, quantified, and analyzed the differences in DNA TMs identified in the five major tumor types mentioned above. In addition, this article explores the mechanisms and principles of DNA tumor biomarker types with relative commonality and specificity in tumor formation and spread among the five major tumor types. We found that the mechanism characteristics of common TMs in the five major tumor types are relatively concentrated; The mechanism characteristics of TMs unique to the five major tumor types are more dispersed. The frequency of occurrence of DNA tumor biomarker mechanism classification has a certain directional effect on tumor types and has a positive impact on the judgment of tumor types. This study aims to provide theoretical support for the discovery, refinement, and personalized clinical application of more TMs in the future, and to improve the survival rate and quality of life of cancer patients.